Development of front and back rolling mobile learning media for class x students of SMAN 1 Pamekasan - Dwi Akbar Fitriliyanto; Usman Wahyudi; Rama Kurniawan (CV Rezki Media, 2022)
Many students do not understand the gymnastic movements being taught and become bored with the movement, as well as the learning method. This study aims to produce a learning media device in physical education, sports and health in the form of mobile learning floor exercise with front roll and back roll material for student’s class X of SMAN 1 Pamekasan so that it can be a teaching material. In this study, the Research and Development (R&D) from Lee and Owens was. So that only 5 steps are in accordance with the conditions in the field. (1) needs analysis, (2) product design, (3) development related to the material to be developed (4) application/implementation, (5) product evaluation by experts and product trials. Results of product development data obtained the first result (91.3%) with 32 students and the second group (87.4%) with 115 students. From the results of these data, it can be concluded that the criteria for learning media products for floor exercise materials based on mobile learning have very valid criteria and are suitable for use in learning activities in schools.